ECONOMIC ASPECT OF CRIMINAL LAW COUNTERACTION TO JUSTIFICATION OF ARMED AGGRESSION AGAINST UKRAINE: RISKS FOR THE STATE BUDGET IN THE LIGHT OF THE PRACTICE OF THE EUROPEAN COURT OF HUMAN RIGHTS - Andrii Lapkin; Daryna Yevtieieva; Daria Kukovynets (Baltic Journal of Economic Studies)
Research subject. The scientific article analyses the economic aspect of criminal law enforcement in the context of the Russian Federation's armed aggression against Ukraine and associated actions. It examines the potential financial implications for the Ukrainian state budget in relation to the settlement of compensation claims arising from violations of the Convention for the Protection of Human Rights and Fundamental Freedoms of 1950 (hereinafter referred to as the Convention). The criminal law is employed to combat justification, as well as to recognise the legitimacy of the denial of the armed aggression of the Russian Federation against Ukraine and the glorification of its participants. This is achieved through the application of Art. 4362 of the Criminal Code of Ukraine (henceforth – CCU). In this regard, the objective of the present study is to predict the potential financial compensation that may be granted by the European Court of Human Rights (hereinafter – ECHR) in such cases, and the ensuing financial implications for the state budget of Ukraine, which will assume the financial responsibility for the relevant expenditures. In order to achieve this objective, the compliance of Art. 4362 of the CCU by the provisions of Articles 3, 5, 8 and 10 of the Convention and the practice of the ECHR was checked. Мaterials and methods. The empirical basis of the study was as follows: (1) statistical data on Ukraine's participation as a defendant in the ECHR and the expenses incurred by it for the compensation of damages in 2019-2023; (2) approximately 900 verdicts of Ukrainian courts under Article 4362 of the Criminal Code; (3) the survey results of 4015 law enforcement officers of Ukraine on countering the glorification of the Russian armed aggression in Ukraine; (4) the survey results of 16 Ukrainian judges on countering the glorification of the Russian armed aggression in Ukraine; (5) 46 ECHR judgments. The following methodological approaches were employed: dialectical, inductive and deductive reasoning, analysis and synthesis, and economic analysis. Results. It has been determined that the criminal law provisions stipulated in Article 4362 of the CCU, by virtue of their subject matter and nature, give rise to the potential for restrictions on the rights to privacy (Article 8), freedom of speech and expression (Article 10), and, in a indirect capacity, the prohibition of torture (Article 3) and the liberty and security of the person (Article 5) as guaranteed by the Convention. Consequently, this may result in a negative economic effect, manifesting as potential expenditures from the state budget for the purpose of compensating individuals who have been subjected to violations of the aforementioned Convention provisions. Based on the average amount of compensation in cases against Ukraine of 13,190.8 EUR and the number of convictions under Article 4362 of the CCU, as well as taking into account the factors that may affect the number of applications to the ECHR by persons convicted under this Article, an approximate total amount of possible satisfaction was calculated in the range of 264,000 EUR - 923,000 EUR. At the same time, this amount could reach up to 18 million EUR, assuming that all convicted persons bring an action.